2012
DOI: 10.1039/c2sm26334c
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of emulsions: diffusion and particle size distribution using diffusing wave spectroscopy and diffusion using nuclear magnetic resonance

Abstract: Diffusing wave spectroscopy (DWS) is one of the few techniques enabling the investigation of structures and dynamics in turbid systems that is in the multiple light scattering domain. This makes it an important technique to study colloidal dispersions such as foam, gel or emulsion. In this article, DWS in both back-and forward-multiple scattering was used to monitor the in vitro digestion of turbid undiluted emulsions. Eight formulations were tested using two triglycerides, two emulsifiers and two emulsifier c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
3
24
1
Order By: Relevance
“…This indicates an increase of the viscosity of the aqueous medium, in agreement with the decreased diffusion coefficient of PC/T80 droplets. A decrease of water diffusion coefficient upon incubation in simulated digestive conditions has previously been observed , but digestion is accompanied of very large change of the molecular and supramolecular structures. Desorption of Tween‐80 molecules due to the decrease of total surface area of the droplets with coalescence could participate to this phenomenon.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…This indicates an increase of the viscosity of the aqueous medium, in agreement with the decreased diffusion coefficient of PC/T80 droplets. A decrease of water diffusion coefficient upon incubation in simulated digestive conditions has previously been observed , but digestion is accompanied of very large change of the molecular and supramolecular structures. Desorption of Tween‐80 molecules due to the decrease of total surface area of the droplets with coalescence could participate to this phenomenon.…”
Section: Resultsmentioning
confidence: 67%
“…The mobility of the TAG molecules inside the oil droplets is hindered because of the viscosity of the lipid phase, whereas the diffusion of PL is restricted to their lateral diffusion within the interfacial monolayer, as determined by its microfluidity. The coefficients were lower than diffusion coefficients at 37°C of triolein in emulsions (mean droplet size varying between 350 and 400 nm) stabilized by sodium oleate or β‐lactoglobulin (around 1 × 10 −11 m 2 s −1 ) . This difference could result from a higher viscosity of our lipid blends as compared to triolein, including a temperature effect.…”
Section: Resultsmentioning
confidence: 74%
“…In the transmission mode, scattered light is detected after passing through the sample, and intensity fluctuations are correlated using the correlation intensity function (ICF). In contrast, in the backscattering mode, the light that disperses back towards the incident beam is collected and its fluctuations are measured [43][44][45].…”
Section: Materials and Methodology Of Studiesmentioning
confidence: 99%
“…Forward-scattering DWS measurements, complementary to nuclear magnetic resonance diffusion measurements, permitted to determine the diffusion coefficients. It was observed that during digestion, the transitions were from a droplet to a vesicle and afterwards to a micelle [174].…”
Section: Spectral Properties Of Emulsionsmentioning
confidence: 99%